Volume 3: Fluid Mechanics; Micro and Nano Fluid Dynamics; Multiphase Flow 2021
DOI: 10.1115/fedsm2021-66013
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Elbow Erosion Mitigation Using Swirl Pipes in Gas-Particle Two-Phase Flows

Abstract: In the oil and gas industry, sand particle erosion damage to elbows is a common problem. The ability to predict erosion patterns is of great importance for sizing lines, analyzing failures, and limiting production rates. Computational fluid dynamics (CFD) can be utilized to study the erosion behavior and mitigate the erosion problem for safety purposes and greater equipment longevity. In order to alleviate the adverse results of sand erosion in elbows, the current study investigated the potential of the geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results revealed that the erosion rate in the elbows in the twisted piped was less than the achieved value for the standard one. Also, the maximum erosion rate decreased when the location of the twisted pipe was close to the elbow (Farokhipour, Mansoori, Saffar‐Avval, & Ahmadi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the erosion rate in the elbows in the twisted piped was less than the achieved value for the standard one. Also, the maximum erosion rate decreased when the location of the twisted pipe was close to the elbow (Farokhipour, Mansoori, Saffar‐Avval, & Ahmadi, 2021).…”
Section: Introductionmentioning
confidence: 99%